The Literature Archive of the Future: Statements and Perspectives - Richter, Sandra (Wallstein Verlag, 2023)
How can literary archives adapt to the challenges of the future? Literary archives are per se international because their subject is international. Literature does not end at the borders of its country of origin or its language. Hence, literary archives hold material that is not limited to a country or a language, although one country and language is usually dominant. It might even be the case that an archive has the official task of preserving the literary heritage of a specific territory and is funded for this purpose. How can we conceptualize literary archives in their regional and global frameworks and develop them further? To what extent does digitization foster international cooperation within and beyond the archives and how can we make it more fruitful? How can archives meet the interests of the literary public and of researchers? With contributions by: Stephen Enniss, Lavinia Frey, Jeang-Yean Goak, Ben Hutchinson, David D. Kim, Stefan Litt, B. Venkat Mani, Nelson Mlambo, Sebastian Möring, Sandra Richter, Fred Studemann, Meike G. Werner, Katja Wiesbrock Donovan